INCREASE OF DEMAND FOR GRADUATES OF HIGHER EDUCATION INSTITUTIONS - Ruslan A. Abramov; Irina V. Pronina; Elena Yu. Khalatenkova (Russian State Vocational Pedagogical University, 2017)
Abstract. The aim of the research is identification of the objective and subjective factors influencing professional self-realization of graduates of the field of study «Public and Municipal Administration».Methods. The authors have conducted anonymous opinion survey of prestigious economic universities undergraduates (bachelor and master degree course) and graduates specialized in this sphere. The questions were about correspondence of gained academic qualification and actual occupation, the importance of degree certificate, satisfaction with education quality, attitude to different aspects of studying etc. In order to make relevant conclusions, the authors apply comparative, statistical, eneralization and induction methods.Results. Informants' answers helped to count out the percentage of graduates whose occupation is connected with public administration, understand the reasons of choosing relevant master course, assess the significance of acquired competence and qualification for job placement at governmental organizations. The main scientific result of the research is working out a system of recommendations aimed at increasing demand for graduates specialized in the sphere of civil service, and, consequently, improving the efficiency of investment in management training. It is specified that the most important issues in this regard are forethought of career choice, students' vision of academic planning, and approach to teaching, practice-oriented type of education.Scientific novelty. Having organized the data and compared it with previous surveys' results, the authors reveal the factors essential to professional success and application of knowledge as well as correlation of these factors which means meeting the objective of the research.Practical significance. The presented materials can be used for the further modernization of the process of educational planning and taken into notice while developing academic programs for the direction «Public and Municipal Administration».